Developing English learning materials for computer network engineering students at peripheral Indonesia - Andri Prayoga; Dedi Irwansyah; Trisna Dinillah Harya (EduLite: Journal of English Education, Literature and Culture, 2021)
This research was aimed at developing and validating English learning materials for students of computer network engineering of Vocational High School (VHS) at peripheral city of Indonesia.  This study followed the Research and Development (R&D) method. It involved three experts in the field of English instruction, ten students and one English teacher of Vocational High School (VHS) Teladan Metro, Lampung which was considered as a peripheral part of Indonesia. The research data were drawn from questionnaire distributed to the students, an interview conducted to the English teacher, and the developed materials which had been validated by the experts. The findings of the research show: (1) the development of English learning materials for computer networking should be centred around the students’ learning needs; (2) a prompting visuals aspect and a clear map of the course book are what make the developed course book more acceptable, and (3) experts validation of the developed course book enhances its readability and acceptability. It is recommended that English teachers of VHS would design their own supplementary learning materials as the nation-wide use materials might not cover all of the students’ learning needs.